The sensitivity and specificity of three pregnancy-associated glycoprotein ELISA assays and factors affecting test accuracy in South African dairy cows - Irons, Pete Charles (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.